Simulation of school business process - Usman Jeylani; Muhammad Falihul Isbah; Muhammad Ainul Yaqin; Pinkan Veri Diana E (Journal of Engineering and Applied Technology, 2020)
School is an institution where people learn reading, writing, and learning to have good character. The school has a social interaction system in an organizational relationship. Every institution must have a business process to achieve its vision and mission. The business process has activities carried out to provide services or products. This study analyzes business process systems in schools by designing school business process simulation scenarios and then implementing the design of AnyLogic Software and it can contribute to optimizing the management of business processes within schools, where processes are more structured and systematic. The method used in this study is the Business Process Improvement (BPI) Method to eliminate errors and provide competitive benefits by improving business processes. In applying the BPI method, the results obtained are recommendations for improving school business processes: (1) Adding Buses to schools, (2) Adding School Cooperative Staff to transport goods, and (3) Adding Cashiers in School Cooperatives.